A novel fast power swing blocking strategy for distance relay based on ADALINE and moving window averaging technique - Mohsen Jannati; Mohammad Mohammadi (IET Generation, Transmission & Distribution, 2021)
Abstract This study proposes a a novel efficient strategy for identifying symmetrical faults from power swings in order to improve the performance of distance relay. This method is based on two new indices and the use of adaptive linear neuron and moving window averaging technique, which is applied to the waveforms of the current. If the proposed algorithm detects power swings, it enables power swing blocking; and if it recognises the occurrence as a symmetrical fault, it resets the power swing blocking as quickly as possible. The efficiency of the proposed method has been tested in different conditions and compared to other methods from different points of view. Simulation results under different conditions in PSCAD and MATLAB software show that the proposed strategy is able to detect symmetrical faults from power swings with high accuracy. The high robustness of adaptive linear neuron and the moving window averaging technique has made the proposed method highly noise‐resistant; and also, because of its low computational cost, the response speed of the proposed strategy is very high, and hence its practical implementation is simple.